2021
DOI: 10.1186/s12943-021-01366-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel induction of CD40 expression by tumor cells with RAS/RAF/PI3K pathway inhibition augments response to checkpoint blockade

Abstract: Background While immune checkpoint blockade (ICB) is the current first-line treatment for metastatic melanoma, it is effective for ~ 52% of patients and has dangerous side effects. The objective here was to identify the feasibility and mechanism of RAS/RAF/PI3K pathway inhibition in melanoma to sensitize tumors to ICB therapy. Methods Rigosertib (RGS) is a non-ATP-competitive small molecule RAS mimetic. RGS monotherapy or in combination therapy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 73 publications
4
31
0
Order By: Relevance
“…2 C). These results match well with the observation that RAS/RAF/PI3K pathway inhibition increased CD40 expression in melanoma cells [ 2 ].
Fig.
…”
Section: Cd40 Regulation and Connection To Ras/raf/pi3k-targeted And Immune Therapiessupporting
confidence: 92%
See 3 more Smart Citations
“…2 C). These results match well with the observation that RAS/RAF/PI3K pathway inhibition increased CD40 expression in melanoma cells [ 2 ].
Fig.
…”
Section: Cd40 Regulation and Connection To Ras/raf/pi3k-targeted And Immune Therapiessupporting
confidence: 92%
“…CD40, also known as TNFRSF5, is a co-stimulatory cell surface receptor present on antigen-presenting cells (APC), non-hematopoietic cells (e.g., myofibroblasts, fibroblasts, epithelial, and endothelial cells) and tumor cells [ 1 , 2 ]. The CD40 and CD40 ligand (CD40LG) interaction mediates anti-tumoral immune responses by increasing immunogenic cell death (ICD) of tumor cells, APC activation, tumor immunogenicity by up-regulating major histocompatibility complex (MHC) molecules, production of proinflammatory factors, costimulation of CD4 + and CD8 + T cells, and tumor cell susceptibility to T-cell lysis [ 2 – 4 ]. Recently, our group demonstrated that RAS/RAF/PI3K pathway inhibition promotes ICD and augments response to immune checkpoint blockade (ICB), which mechanistically relies on CD40 induction by melanoma cells [ 2 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…TCGA project and GEO database provide large-scale molecular distortion data of DNA, RNA, protein, and epigenetic levels in various types of tumors that aid in understanding potential carcinogenic molecular mechanisms; this data is widely used in studies of various tumors including GC [ 29 32 ]. In the present study, we first identified the GC-associated lncRNA FAM225A by analyzing data from TCGA and the GEO database, which suggested that FAM225A was overexpressed in GC tissues.…”
Section: Discussionmentioning
confidence: 99%